Pancasila as the cultural traits for Indonesian national religious identity in the era of globalization - Tatit Hariyanti (Universitas Islam Sultan Agung, 2020)
This paper is library research attempting to explore the way to maintain the local identity in globalization for Indonesian particularly their national religious identity. Taking and tracking documents in the form of data relating to the issues of globalization, religious identity, and Pancasila and adopting the concept of grounded globalism by James L. Peacock which affirms and seeks embodied connectedness to locale, this paper shares the perspective that Pancasila is still qualified and deserve to be used as a basic foundation to maintain and strengthen the national religious identity of the Indonesian people in the global era. Indonesia does not need to be transformed by global identity. Indonesia has already had its own national religious identity which is global. The five principles of Pancasila need to be actualized as the ground and cultural traits of their global identity. By grounding global identity on Pancasila, Indonesians can enjoy globalization without losing its national identity.